Problem Solving Learning Model in Improving Civic Education Learning Outcomes in Supian Private Vocational School - Ritonga, Cindy Dwi; Adi, Panggih Nur (Prisma Sains : Jurnal Pengkajian Ilmu dan Pembelajaran Matematika dan IPA IKIP Mataram, 2024)
This study aimed to assess the academic performance of Class XI2 students enrolled at Supian Private Vocational School located in Silangkitang Building. The research methodology employed was classroom action research, focusing on students from Class XI2 at Supian Pembangunan Silangkitang Private Vocational School. The study utilized the Kurt Lewin model, consisting of four cycles: planning, implementing actions, observation, and evaluation. Data collection methods included observation and testing. In the initial cycle, the average observation score indicated a low level of student engagement, with only 31.14% of students categorized as actively participating. However, in the subsequent cycle, this figure increased to 65.4%, demonstrating significant improvement in student activity following the implementation of the problem-solving learning model. Moreover, in the third cycle, the percentage of students achieving the required level of proficiency reached 84.2%, surpassing the 80% benchmark. Consequently, students in Class XI Semester II at Supian Private Vocational School in Silangkitang Building achieved satisfactory academic results.